TRAINING OF POLICY EVALUATION STUDIES - Muhamad Suhardi, Nada Nazopah, dan Syafaat Ariful Huda (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2020)
The purpose of this policy study is to know the difference between policy program and policy implementation in field. This evaluation study is using policy evaluation approach. In the quality assurence reference completeness component, governance, human resource development, excellency, and public image improvement has not achieved yet such as; inadequate insfrastructure, operational standard has not been standardized, low quality human resources, inadequate fund to training and further studies, acces to attending national and international seminars has not been created, learning resources are not used maximally, lecturers’ teaching and research ability are still low, community services is still in traditional ways, curriculum has not directed to labor market and ready-working graduates yet, new adminssion system has not gone well, evaluation has not gone well, inconsistency of journal content, outstanding service has not been going well.